Cross sectional study of depression, anxiety and stress due to COVID-19 pandemic among undergraduate medical students from Maharashtra - Waghmare, Paras R.; Ukey, Ujwala U.; Sharma, Sarita K.; Meman, Sumaiya A. (International Journal Of Community Medicine And Public Health, 2021)
Background: The ongoing pandemic due to novel corona virus has caused global social and economic disruption, including the largest global recession since the great depression. Pandemic has led to essential supply shortage like daily needs medicine that led to haphazard among population. Worldwide increase in case numbers have increases anxiety among population and also increase the tremendous stress among students due to lack of educational activity. This affects psychology of students to move away from studies. Due to pandemic many students were unable to attend clinics that create anxiousness among them which led to anxiety and stress. Methods: The survey was conducted among the undergraduate medical students across the state of Maharashtra. The online semi-structured questionnaire was developed with the aid of Google form, among various undergraduate medical students by using DASS-21 scale. Results: In the present study, total 435 students responded and returned completely filled in questionnaire. Out of these 435 study participants, 213 (48.97%) were male students and remaining 222 (51.03%) were female students. Based on responses to the DASS-21 scale, study participants can be categorized as normal or with mild, moderate, severe and extremely severe depression, anxiety or stress. Conclusions: The present study concludes that psychological health of the undergraduate medical students who participated for the survey is involved to a sizeable extent. Depression and anxiety and some or other degree of stress was detected in the participants as a common finding.